Improving Clinical Laboratory Safety Knowledge Through Multi-Modal Interventions - Weiderman, Brian (My University, 2025)
This project examined the safety culture of the clinical laboratory at Irwin Army Community Hospital and worked to strengthen it through evidence-based interventions. The project starts by creating a safety knowledge and culture survey based on requirements from OSHA, CLIA, CAP, the Joint Commission, and CDC. Twelve staff members across multiple laboratory sections completed the assessment. Their responses showed that the laboratory has a solid foundation in areas such as PPE use, equipment safety, and emergency procedures, but also revealed several important gaps. The most notable weaknesses involved the use and verification of biosafety cabinets and fume hoods, waste management, and the steps required after an exposure or patient identification error. Most staff viewed the laboratory’s overall safety culture positively. Using these results, targeted training tools were used in the form of fact sheets, direct communication, and training lessons to address both immediate training needs and longer-term system improvements. Early feedback showed that staff confidence improved, particularly in the areas identified as weaknesses. Taken together, the project demonstrates that a focused assessment combined with practical training materials can meaningfully improve laboratory safety knowledge and help build a more consistent and proactive safety culture.
Keywords: laboratory safety; safety culture; biosafety; chemical hygiene; occupational health; regulartory standards